2021
DOI: 10.1044/2021_jslhr-20-00153
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Emotion Recognition and Word Recognition in Background Noise

Abstract: Purpose Word recognition in quiet and in background noise has been thoroughly investigated in previous research to establish segmental speech recognition performance as a function of stimulus characteristics (e.g., audibility). Similar methods to investigate recognition performance for suprasegmental information (e.g., acoustic cues used to make judgments of talker age, sex, or emotional state) have not been performed. In this work, we directly compared emotion and word recognition performance in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 63 publications
2
13
2
Order By: Relevance
“…This suggests that to reach recognition threshold in noise, emotional semantics call for an addition of ∼3.3 dB SNR as compared to emotional prosody. This prosodic advantage across age groups expands previous evidence that focused mainly on an accuracy advantage for prosodic recognition over spoken word recognition ( Dupuis and Pichora-Fuller, 2014 ; Morgan, 2021 ; Morgan et al, 2022 ). A noteworthy study by Morgan (2021) reported a 10 dB SNR advantage between emotional prosodic thresholds and spoken word identification thresholds in young adults.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…This suggests that to reach recognition threshold in noise, emotional semantics call for an addition of ∼3.3 dB SNR as compared to emotional prosody. This prosodic advantage across age groups expands previous evidence that focused mainly on an accuracy advantage for prosodic recognition over spoken word recognition ( Dupuis and Pichora-Fuller, 2014 ; Morgan, 2021 ; Morgan et al, 2022 ). A noteworthy study by Morgan (2021) reported a 10 dB SNR advantage between emotional prosodic thresholds and spoken word identification thresholds in young adults.…”
Section: Discussionsupporting
confidence: 84%
“…This prosodic advantage across age groups expands previous evidence that focused mainly on an accuracy advantage for prosodic recognition over spoken word recognition ( Dupuis and Pichora-Fuller, 2014 ; Morgan, 2021 ; Morgan et al, 2022 ). A noteworthy study by Morgan (2021) reported a 10 dB SNR advantage between emotional prosodic thresholds and spoken word identification thresholds in young adults. This marks a much larger advantage than the 3.3 dB SNR difference we report.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations